Impacts of information technology on patient care and empowerment - McHaney, Roger; Reychav, Iris, 1969-; Azuri, Joseph, 1972-; McHaney, Mark E.; Moshonov, Rami (Advances in medical technologies and clinical practice book series., 2020)
"This book examines existing challenges as well as potential opportunities for improving patient care, empowerment, personalization, and outcomes through emerging health information technology"--Provided by publisher